Mechanical behavior of different restorative materials and onlay preparation designs in endodontically treated molars - de Carvalho, Ana Beatriz Gomes [UNESP]; de Andrade, Guilherme Schmitt [UNESP]; Tribst, João Paulo Mendes; Grassi, Elisa Donária Aboucauch [UNESP]; Ausiello, Pietro; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Bressane, Adriano [UNESP]; de Melo, Renata Marques [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (MDPI, 2021)
This study evaluated the effect of the combination of three different onlay preparation designs and two restorative materials on the stress distribution, using 3D‐finite element analysis. Six models of first lower molars were created according to three preparation designs: non‐retentive (nRET), traditional with occlusal isthmus reduction (IST), and traditional without occlusal isthmus reduction (wIST); and according to two restorative materials: lithium‐disilicate (LD) and nanoc-eramic resin (NR). A 600 N axial load was applied at the central fossa. All solids were considered isotropic, homogeneous, and linearly elastic. A static linear analysis was performed, and the Maximum Principal Stress (MPS) criteria were used to evaluate the results and compare the stress in MPa on the restoration, cement layer, and tooth structure (enamel and dentin). A novel statisti-cal approach was used for quantitative analysis of the finite element analysis results. On restoration and cement layer, nRET showed a more homogeneous stress distribution, while the highest stress peaks were calculated for LD onlays (restoration: 69–110; cement layer: 10.2–13.3). On the tooth structure, the material had more influence, with better results for LD (27–38). It can be con-cluded that nRET design showed the best mechanical behavior compared to IST and wIST, with LD being more advantageous for tooth structure and NR for the restoration and cement layer.
Keywords: Dental materials; Dental onlays; Dental prosthesis; Finite element analysis; Mechanical stress